Paradigm Shift in Nomination Thresholds and Electoral Justice Reconstruction: An Analysis of Constitutional Court Decision Number 60/PUU-XXII/2024 - Junaidin; Iwan Satriawan; Nanik Prasetyoningsih (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2024)
This research aims to comprehensively examine the ratio decidendi of Constitutional Court (MK) Decision Number 60/PUU-XXII/2024, focusing on its relevance to the theory of electoral justice. This research uses a descriptive-analytical normative legal approach, a literature review of primary and secondary legal materials, and an in-depth qualitative analysis. The main findings indicate that Constitutional Court (MK) Decision Number 60/PUU-XXII/2024 marks a fundamental paradigm shift in determining regional head nomination thresholds, moving from a seat/vote acquisition basis to a population size basis, which aims to reconstruct procedural and distributive justice in the electoral system. This shift addresses distortions in nomination access that previously favoured established parties, creating a more level playing field and enhancing representation and choice for voters. The usefulness of this research is to help understand how nomination thresholds can cause procedural injustice and how judicial intervention can correct these distortions. By examining the shift in thresholds to a population basis, this research highlights how the Constitutional Court's decision can change the philosophy of nominations, encourage healthier participation and competition, and strengthen the legitimacy of election results. It also shows how court decisions can reshape the distribution of political opportunities.